Pengaruh Latihan Penguatan Dengan Elastic Band Dalam Meningkatkan Kemampuan Pasien Osteoarthritis Knee Di Rumah Sakit Condong Catur Sleman - Wahyuni, Wahyuni; Zakaria, Ricky Fauzi (FISIO MU: Physiotherapy Evidences, 2021)
Background Osteoarthritis is a degenerative disease caused by joint cartilage damage. The main symptoms of osteoarthritis are pain and movement disorders that can affect the functional disorders. The prevalence of knee osteoarthritis in Indonesia is quite high reaching 15.5% in men and 12.7% in women. It is estimated that 1 to 2 million older people in Indonesia suffer from disabilities due to osteoarthritis. Osteoarthritis treatment is intended to reduce pain improve functional ability and prevent deformity. Elastic band strengthening exercises are exercises that can be used to reduce pain increase muscle strength and functional ability. Objective This study aims at determining the effect of elastic band strengthening exercises in improving knee osteoarthritis functional capabilities. Method The method used in this study was quasi-experimental with pre and post-test control group design. The number of respondents of this study was 20 respondents diagnosed with knee osteoarthritis in Condong Catur Hospital Sleman. Respondents were randomly divided into two groups namely the treatment group that received elastic band strengthening exercise treatment and the control group that received standard treatment given at the hospital. The treatment was given twice a week for four weeks. Measurement of functional ability was done using WOMAC score. Results There was a decrease in pain level in the treatment group while in the control group the pain level was still the same as before. In the functional ability there was an increase in the treatment group. The statistical test showed that there was an influence between the treatment group and the control group. Conclusion Elastic band strengthening exercises effectively improved functional capabilities in knee osteoarthritis in Condong Catur Hospital Sleman. Keywords elastic band strengthening exercises functional capabilities knee osteoarthritis